Long-Term Clinical Outcomes of Percutaneous Transluminal Angioplasty with Optional Stenting in Patients with Superficial Femoral Artery Disease: A Retrospective, Observational Analysis. (November 2018) - Vossen, Rianne J.; Vahl, Anco C.; Leijdekkers, Vanessa J.; Montauban van Swijndregt, Alexander D.; Balm, Ron
Abstract : Background and objective: The recent ESC guideline advises primary stent placement in superficial femoral arterial disease (SFAD). The aim of this study was to compare clinical outcomes of SFAD patients selected for stent placement with plain percutaneous transluminal angioplasty (PTA). Materials and methods: A single centre retrospective, observational analysis was performed of all consecutive patients undergoing endovascular treatment for SFAD from 2004 to 2015. Primary endpoints were primary and secondary clinical patency rates in patients with or without stent placement. Secondary endpoints were recurrence rates and number of amputations. Kaplan–Meier curves were used to compare patency rates. Multivariable Cox regression analysis was performed to adjust for confounding variables and to identify variables associated with loss of patency. Results: A total of 389 patients were analysed with a median follow up of 42 months. Two hundred and fifty one patients (64.5%) were stented. Primary clinical patency rates at 1, 3, and 5 years were 82.8%, 71.0%, and 65.6% after PTA and 76.3%, 65.7%, and 58.1% after stent placement (PTA-S), respectively ( p = .30). Secondary patency rates were also comparable for the PTA and PTA-S group resulting in 1, 3 and 5 year clinical secondary patency of 89.1%, 81.0%, and 76.3% in the PTA group versus 87.8%, 78.5%, and 71.9% in the PTA-S group ( p = .58). Multivariable analysis revealed equal primary and secondary clinical patency between the treatment groups. The absolute re-intervention rate was 29.3%. The number of re-interventions and amputation rate did not significantly differ between the two groups ( p = .41 and p = .75). Conclusions: Selective stenting in patients with SFAD shows comparable results in long-term clinical outcomes in patients who were treated with plain PTA as well as patients who are selected for stent placement. An approach of selective stenting is justified.